Feasibility of Offshore Wind Energy in Turkey; A Case Study for Gulf of Edremit at the Aegean Sea - Ozbek, Muammer; Tunc, Kerim Mehmet Murat (Gazi Univ, 2021)
This work aims to investigate the feasibility of offshore wind energy in Turkey by performing extensive simulations and analyses for a 50-90 MW capacity offshore wind park to be constructed at the Gulf of Edremit, a very high potential site located at the Aegean Sea, 3 km from the west coastline of Turkey. The location and layout of the farm is optimized by considering the sea depth data obtained from bathymetric maps and wind speed measurements acquired from the MERRA data and local met mast. Dynamic interactions among the turbines and the resulting wake losses are modeled by using two different site assessment programs. Capacity factors and the annual energy production yields are calculated for 8 different types of turbines with rated powers changing between 2 and 3.6 MW.
Keywords: Wind Energy; Offshore Wind Turbine; Cluster/Farm Design; Fluid Mechanics; Dynamic İnteractions; Farm; Optimization; Generation; State